How to help more : effects of glucose-rinse and autonomous motivation on prosocial behaviour - Lim, Samantha Jing Xian (2014)
Glucose-rinsing and prosocial behaviours have been separately studied in past research, and this study aims to join these two fields of work together. Specifically, the effects of glucose-rinsing and motivation on actual prosocial behaviour will be examined in the present study. Seventy-nine undergraduates between ages 19 to 24 years were administered with either a glucose solution or placebo solution prior to an unexpected helping episode, during which a confederate requested for help in a title generation task. On behalf of the confederate, the experimenter solicited help from each participant. The requests for help were phrased differently to place participants in either an autonomous motivation or controlled motivation condition. Results showed no significant effect for rinsing and motivation to help. However, there was a marginally significant interaction effect between rinsing and prosocial motivation on helping behaviour. The findings suggest that glucose-rinsing acts as a moderator between prosocial motivation and prosocial behaviour. Participants with autonomous prosocial motivation had the highest helping performance when they rinsed with glucose solution. Interestingly, findings also revealed that controlled prosocial motivation eliminated the positive effects of glucose rinsing as individuals would offer help regardless of the solution being rinsed. Consequently, the use of glucose-rinsing would be beneficial in the helping domain, particularly for individuals who already have autonomous prosocial motivation.